2022
DOI: 10.1097/md.0000000000029486
|View full text |Cite
|
Sign up to set email alerts
|

Intramuscular administration of autologous total immunoglobulin G induces immunomodulatory effects on T cells in healthy human subjects

Abstract: Background:We hypothesized that intramuscular administration of autologous total immunoglobulin G (IgG) could induce an immunomodulatory effect in human subjects. In our previous studies, we showed that intramuscular administration of autologous total IgG could induce significant clinical improvements and increases of the serum levels of interleukin-10 (IL-10) and interferon-gamma (IFN-γ) in patients with atopic dermatitis.Objective:To investigate the mechanism of immunomodulation induced by intramuscular admi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…Previously, our research group demonstrated that the human thymus can generate IL-10-producing regulatory B cells (B10) in response to stimulation with polyclonal IgG from individuals with allergies 18 . In recent years, the immunomodulatory effects of polyclonal IgG have been observed both in vitro 30 34 and in vivo 35 38 , primarily focusing on T cell populations in murine and human systems.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, our research group demonstrated that the human thymus can generate IL-10-producing regulatory B cells (B10) in response to stimulation with polyclonal IgG from individuals with allergies 18 . In recent years, the immunomodulatory effects of polyclonal IgG have been observed both in vitro 30 34 and in vivo 35 38 , primarily focusing on T cell populations in murine and human systems.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, 13 healthy adults were submitted to an intramuscular administration of total autologous IgG in the same protocol used in the above AD patients’ studies (50 mg for 4 weeks). These individuals demonstrate an increase in the percentage of peripheral CD4+ T cells producing IL-10 and CD3+ T cells producing IFN-γL-10 compared to baseline [ 43 ]. Unfortunately, the researchers did not evaluate complex intracellular and phenotypic molecules to generate more analytical aspects that may be compared or corroborated with the complexity of experimental evidence.…”
Section: In Vivo Approaches To the Immune Tolerance Induced ...mentioning
confidence: 99%
“…In humans, an author of this review (Nahm DH) reported that the intramuscular administration of autologous total IgG increased the percentage of IL-10-producing CD4 + T cells in the peripheral blood in 13 healthy human subjects ( 46 ). However, this report could not provide a detailed molecular mechanism underlying the autologous polyvalent IgG-mediated immunomodulation or the subpopulation of Treg cells activated by autologous polyvalent IgG.…”
Section: Four Hypothetical Models For the Mechanism Underlying Polyva...mentioning
confidence: 99%
“…In a clinical trial, IVIg therapy in patients with common variable immunodeficiency significantly increased the number of peripheral Treg cells (expressing CD4, CD25, and low levels of CD127) and plasma levels of IL-10 within 30 minutes after the infusion of IVIg, suggesting a highly efficient interaction between polyvalent IgG and Treg cells ( 64 ). This review provides a summary of study results (subpopulation of Treg cells and mechanism) on the polyvalent IgG-induced activation of Treg cells in human clinical trials ( Table 3 ) ( 46 , 57 65 ).…”
Section: Evidence Supporting Activation Of Treg Cells By Polyvalent I...mentioning
confidence: 99%
See 1 more Smart Citation